A survived case of fulminant alcoholic hepatitis with multiple organ failure (MOF) - SATO, Hitoshi; TOMARU, Hisashi; NARISAWA, Tsuneo; KUROSAWA, Mitsutoshi; SUGIMURA, Iwao; FUKUI, Minoru; FURUKAWA, Tomoyuki; SEKIYA, Chihiro; NAMIKI, Masayoshi (Kanzo, 1987)
A survived case of a 60-year-old man who is habitual alcoholism rapidly fell into MOF with acute hepatic insufficiency due to excess alcoholic ingestion was reported. I thought this case acute hepatic failure on chronic liver disease (acute on chronic) by Sherlock. He had history of chronic alcoholic ingestion more than 80g of ethanol per day for twenty five years. He was admitted to our hospital because of fever, abdominal pain and icterus. On admission, hepatomegaly and vascular spiders on the skin were recognized. During clinical course, ascites and bleeding spots on the skin were recognized and his consciousness level was assessed in grade 3 hepatic encephalopathy. This case showed MOF which included acute hepatic insufficiency, disseminated intravascular coagulation, renal failure, gastrointestinal bleeding and heart failure. Plasma exchange, prednisolone and glucagon-insuline therapy were applied for acute hepatic insufficiency. The administration of gabexate mesilate was used for DIC. Peritoneoscopic and liver biopsy examination was findings of alcoholic hepatitis. This patient was a rare survived case of fulminant alcoholic hepatitis with MOF.